Evaluation Effectiveness of Information Systems Implementation At the Faculty of Engineering Hasanuddin University - Minasari Minasari; Muhammad Asdar; Muhammad Yunus Amar (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
This study aims to determine the level of evaluation effectiveness application of information systems at the Faculty of Engineering, Hasanuddin University. This research is a qualitative descriptive study with a survey method, the sample used by 172 respondents from Lecturers, Employees, and Undergraduate Students in the Faculty of Engineering, Hasanuddin University. The research data was obtained from a questionnaire (primary), brainstorming, literature study, and direct interviews with relevant parties according to the research objectives. Analysis of the data used in this study is a SWOT analysis (strength, opportunity, weakness, threat) to formulate an academic information technology system development strategy. The results of this study indicate that the total score for internal strength factors is 3.02. This number is needed as a process to find out where the intersection point (E) in the SWOT Diagram is. The total score for the internal weakness factor is 2.55. This number is also needed as a process to find out where the intersection point (E) in the SWOT Diagram is. Based on the determination of the area, quadrant I is the most extensive, as well as the location of the intersection point located in quadrant I so that the main strategy of developing Information Systems at FT Unhas Makassar is the SO strategy. While alternatives to the development of Information Systems at FT Unhas Makassar are ST, WO, and WT.